Ngangah Imau Tradition in Pulau Tengah Village Kerinci Distric - zahara, siti2; Zahara, Mina (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
The Ngagah Imau ritual in the Middle Island Village community is an ancestral heritage that has been passed down from generation to generation. The purpose of carrying out this ceremony is to pay a wake-up call (compensation) for a dead tiger. What is meant by pay-a-wake is an activity that aims to support the spirit of the tiger or so that other tigers do not descend into the village. The research method functions as a basic reference in conducting research, so that researchers obtain conclusions from the results of existing data analysis. This Research Methods section includes several sub-chapters, namely Types of Research, Research Locations, Determining Research Informants, Types and Sources of Data, Data Collection Techniques and Data Analysis Techniques which will be explained as follows: According to the story of the residents of Pulau Tengah Village, such incidents occurred among the people This kind of ritual is believed by the local community that if a tiger dies in the Kerinci area, it must be protected by the village community, so that other tigers do not come down to the village and prey on livestock or humans. It is said that the beginning of this ritual was that there was a relationship between the Kerinci community and tigers.